The Influence of Digital Marketing, Pricing Strategies, and Product Diversity on Purchase Decisions in Msmes Dins Snack Lamongan - Bella Fernanda; Nurul Badriynah; Titin Titin (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of digital marketing, pricing strategies, and product diversity on purchase decisions in MSMEs at Dins Snack Lamongan. The research method used was quantitative with 100 respondents. The results of the study showed a partial and simultaneous positive and significant influence between the three independent variables on purchasing decisions. Among the three variables, digital marketing has the most dominant influence on purchasing decisions. These findings show the importance of implementing an effective digital marketing strategy, setting the right pricing strategy, and providing an attractive variety of products for Dins Snack Lamongan MSMEs to improve consumer purchase decisions.